12 años de vida de la “Caja Solidaria Nueva Esperanza” en San Bartolomé de Romerillos, cantón Latacunga, Cotopaxi. - Iza Moreno, Nancy Bertha (2017)
The following paper aims to explain the viability of the Caja Solidaria Nueva Esperanza to become a feasible instance for the popular and solidarity economy implementation. The document explains Caja Solidaria Nueva Esperanza process and action in San Bartolomé de Romerillos community, Latacunga canton, Cotopaxi province, as one organization to the community service under a new way of economy. The text emphasizes to response three objectives: a) Identify the main lines of credit for the economic and social strengthening of the community; b) establish policies and regulations that apply to administration and management; c) to know the perception of the founders about Caja Solidaria Nueva Esperanza in its administration, management and services, contrasting them with the traditional financial institutions. At the end of the work it can be seen that community inhabitants are mostly engaged to Caja Solidaria Nueva Esperanza and know it existence through different means. Although there are several challenges to solve, the empowerment and active participation of the partners is evident. It has made that Caja Solidaria Nueva Esperanza grow in organization, administrative capacity and capital. The responsibility that managers have demonstrated, since its foundation, is a fundamental factor for the maintenance of the organization and the consolidation of the trust through partners.